3.118. Rozwiąż równanie: a) x ^ 2 – (3x – 1) ^ 2 = 56x – 43 c) (- 2x – 1)(1 + 2x) = 8 c) 4x – x ^ 2 = 7 ) (2x + 3) ^ 2 = 8x + 8 b) 5x * (x + 2) – 3x = 0 d) (x + 1) ^ 2 – 100 = 0 f) x(x – 2) = x + 2 b) (x + 1) ^ 2 = (x + 1) d) x(2x – 1) = (1 – 2x)(1 + 2x) f) (2x + 1)(2x + 1) = 4 b) ( (3x – 1)(3x + 1) = 10x ^ 2 + 3 d) (2x – 7) ^ 2 = (4x – 1) ^ 2 f) ( (2x – 1) ^ 2 – 3x ^ 2 = 6(x – 4) b) 11 – 14x = (2x + 1) ^ 2 d) 2x ^ 2 + 11x + 21 = (- x + 5)(5 + x) e) (2x – 3)(x + 1) = 1 + (x + 2)(3x – 2) f) (3x – 1) ^ 2 – (2x – 3) ^ 2 + 2(x + 6) = x ^ 2

3.118. Rozwiąż równanie: a) x ^ 2 – (3x – 1) ^ 2 = 56x – 43 c) (- 2x – 1)(1 + 2x) = 8 c) 4x – x ^ 2 = 7 ) (2x + 3) ^ 2 = 8x + 8 b) 5x * (x + 2) – 3x = 0 d) (x + 1) ^ 2 – 100 = 0 f) x(x – 2) = x + 2 b) (x + 1) ^ 2 = (x + 1) d) x(2x – 1) = (1 – 2x)(1 + 2x) f) (2x + 1)(2x + 1) = 4 b) ( (3x – 1)(3x + 1) = 10x ^ 2 + 3 d) (2x – 7) ^ 2 = (4x – 1) ^ 2 f) ( (2x – 1) ^ 2 – 3x ^ 2 = 6(x – 4) b) 11 – 14x = (2x + 1) ^ 2 d) 2x ^ 2 + 11x + 21 = (- x + 5)(5 + x) e) (2x – 3)(x + 1) = 1 + (x + 2)(3x – 2) f) (3x – 1) ^ 2 – (2x – 3) ^ 2 + 2(x + 6) = x ^ 2